O comprometimento organizacional e a remuneração por resultados em um órgão público do Estado de Ceará - Gonçalves, Laura Carolina (2014)
The organizations, concerned with achieving results, look for practices that provide more interaction, participation and commitment of its staff through incentive programs. The variable remuneration enables the alignment between business objectives and the workers, motivating the employee's commitment towards the achievement of organizational goals. In the context of public administration, some agencies have used remuneration policies to compromise servers and enhance results-based management. This study has the general objective to analyze the relative importance of remuneration for results to the commitment of the Secretariat of Finance of the State of Ceará (SEFAZ-CE) server. We conducted a descriptive and analytical study, using a quantitative method, by applying a semi-structured questionnaire based on the instrument by Mayer and Allen, along with SEFAZ-CE servers. The study involved one hundred and ten respondents from various sectors of the Secretariat’s Headquarters I. The data were analyzed quantitatively by MAGIQ (Multi-Attribute Global Inference of Quality), which is a method of multi-criteria decision analysis and through frequency analysis and histograms, sample arithmetic average, sample standard deviation and coefficient of variation. The survey found that the remuneration policy for results at SEFAZ CE is relatively important for the employee's commitment. However, when compared to other factors of commitment, it does not show a major highlight, especially when it is considered an incentive to greater dedication to work. This result may be related to the fact that the results achieved by the organization show no correlation with established performance indicators or they may indicate that the Fiscal Performance Award has little impact on the total remuneration of the server.